2016
DOI: 10.1182/blood-2016-01-687434
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of rVIII-SingleChain: results of a phase 1/3 multicenter clinical trial in severe hemophilia A

Abstract: Key Points rVIII-SingleChain is a novel rFVIII, designed to have high stability and high binding affinity for VWF. In severe hemophilia A patients, rVIII-SingleChain was well tolerated and resulted in low bleeding rates, when dosed twice per week.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

12
146
0
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 78 publications
(159 citation statements)
references
References 23 publications
(36 reference statements)
12
146
0
1
Order By: Relevance
“…In addition, 73.8% of patients remained bleed-free (83.1% free of spontaneous bleeds) during personalized prophylaxis with Nuwiq â in the NuPreviq study. This compares with 45% of patients in the rFVIII-Fc study [19], 39.6% of patients treated with full-length pegylated rFVIII [35], and 43% of patients treated with single-chain rFVIII [36], in studies of a similar duration, and 26.5% of patients treated with full-length rFVIII in a 1-year study [10].…”
Section: Discussionmentioning
confidence: 84%
“…In addition, 73.8% of patients remained bleed-free (83.1% free of spontaneous bleeds) during personalized prophylaxis with Nuwiq â in the NuPreviq study. This compares with 45% of patients in the rFVIII-Fc study [19], 39.6% of patients treated with full-length pegylated rFVIII [35], and 43% of patients treated with single-chain rFVIII [36], in studies of a similar duration, and 26.5% of patients treated with full-length rFVIII in a 1-year study [10].…”
Section: Discussionmentioning
confidence: 84%
“…In the AFFINITY clinical trial program, rFVIII-SC showed excellent hemostatic efficacy with a median annualized bleeding rate (ABR) of 1.14 that is comparable to other recently approved factor products 8. For example, rFVIII-Fc (Eloctate) reported a median ABR of 1.6, and simoctocog alfa (Nuwiq) reported a median ABR of 0.9.…”
Section: Current Factors Available and Extended Half-life (Ehl) Factomentioning
confidence: 96%
“…Moreover, the enhanced affinity for VWF may accelerate the formation of VWF:FVIII complex that not only increases the half-life but also may result in decreased immunogenicity by inhibiting endocytosis of FVIII by dendritic cells 25,26. These modifications resulted in a FVIII molecule with an increased half-life that is comparable to the PEGylated EHL product (Adynovate) 8,10,27,28. When FVIII is normally activated, the heavy and light chains are cleaved and released from VWF.…”
Section: Current Factors Available and Extended Half-life (Ehl) Factomentioning
confidence: 99%
“…The first trial [37] included PTPs with severe hemophilia A 12 years. Participants were allocated to receive either on-demand (n = 27) or prophylactic (n = 146) treatment with rFVIII-SingleChain.…”
Section: Rfviii-singlechainmentioning
confidence: 99%